Specialty choices among new generation of doctors - insights from a Polish survey study - Robert Kupis; Beniamin Michalik; Maciej Polak; Mateusz Kulbat; Alicja Domagała (Scientific Reports)
Abstract The choice of medical specialty for future doctors is a multidimensional issue, associated with many factors. This study aimed to explore the factors influencing the specialty choices of doctors entering the Polish healthcare system. A nationwide cross-sectional survey was conducted from May until August 2023. The data was gathered via an online nationwide survey among recent medical school graduates. We explored respondents’ preferences regarding medical specialties (in two categories: surgical and non-surgical), and the factors that drive their choices. The U-Mann Whitney test was used to compare the distribution of 19 analysed factors, and the chi-squared test was used if a trend was not observed. 737 responses were collected, and 698 were included in the study. The respondents (60.5% female) preferred non-surgical specialties over surgical ones. The main factors influencing doctors’ choices were remuneration, the ability to maintain work-life balance, interest in the medical field, the ability to start a private practice, skills possessed, and doctor-patient interactions. Doctors pursuing a career in surgical fields are driven by slightly different factors than those who chose a non-surgical specialty. The youngest generation values a healthy work-life balance, and their non-professional life remains crucial.